Occupation-Related Injuries Among Healthcare Workers: Incidence, Risk Groups, and the Effect of Training - ERTÜRK ŞENGEL, BUKET; TİGEN, ELİF; BİLGİN, HÜSEYİN; KORTEN, VOLKAN (CUREUS INC, 2021)
Background and objective Occupation-related injuries (ORIs) are undesirable and harmful situations among healthcare workers (HCWs) and may have serious consequences. In this study, we aimed to identify and analyze ORI incidences, risk groups, and the outcomes of a training program to prevent them. Materials and methods Between January 2011 and December 2019, HCWs who applied for infection prevention and control (IPC) due to ORIs (percutaneous needlestick and sharp-object injury or contact with blood or body fluids) were included in the study. Their characteristic features, vaccine histories, injury types, viral serologies, and administered prophylaxis were recorded. After 2014, a periodic ORI training program was started. We used joinpoint regression analysis to compare the ORI incidences before and after the education program. Results During the nine-year study period, 965 ORIs were registered. The mean age of HCWs was 39.3 +/- 8.4 years, and 67.9% of them were female. The total injury incidence for all professions was 34.1 (95% CI: 33.1-37.5) per 1,000 HCWs. The injury incidences were significantly higher in nurses compared to other HCWs (p<0.01). Most of the injuries occurred in the ward setting (37%). HCWs were injured most commonly while administering treatment (36.7%). The trend analysis for the incidence of injuries showed no significant change throughout the study period. The trend in personal protective equipment (PPE) use showed a significant increase (annual percentage change: 1.7, p<0.01). Conclusions The major finding of this study with respect to its implication on the healthcare system is that nurses are an important risk group for ORIs. Although the ORI incidence did not change during the study period, a significantly increased use of appropriate PPE following a systematic training program implementation was observed.
Keywords: blood and body fluid; healthcare workers; needlestick and sharp-object injury; occupational